Analysis of the Use of Social Media as a Promotional Tool to Attract Tourists in the Village of Belitar Seberang - Pratama, M. Ricky; Novianti, Heni; Pramudyasmono, Hajar G; Syaifullah, Syaifullah (Borong Newinera Publisher, 2024)
The study aims to analyze the use of social media as a promotional tool to attract tourists to visit Belitar Seberang Village, Rejang Lebong Regency, Bengkulu. Researchers use a descriptive qualitative approach with data collection techniques of interviews, observations, and documentation studies. Informants were selected through purposive sampling techniques with informant criteria, namely Seberang Village tourism managers, tourism village social media managers, and Seberang Village tour visitors. The data was analyzed using the Miles and Huberman technique. Then the results of the study were analyzed using Herbert Blumer Symbolic Interactionism Theory. The results showed that promotions were carried out on several social media platforms such as Instagram with the account name @desawisatabelitarseberang whose number of followers was 4,065 with several posts 216. Then Facebook Desa Wisata Belitar Seberang which has 835 followers, YouTube channel Desa Wisata Belitar Seberang with 223 subscribers, and Twitter @belirang which only has 4 followers. When viewed from the content uploaded, the number of posts per month is 4 to 5 content and with the number of likes that are also more than other platforms, reaching more than 25 likes per content. All data is taken as of October 16, 2023. Based on these data, it can be seen that Instagram is the platform with the most followers or followers. This means that Instagram is the most effective platform for promoting Sabrang Village tourism to attract tourists.